2016 38th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2016
DOI: 10.1109/embc.2016.7591936
|View full text |Cite
|
Sign up to set email alerts
|

A telepresence wheelchair using cellular network infrastructure in outdoor environments

Abstract: Mobile wireless network technology has grown rapidly over the past decade with emerging applications and services. Particularly, the fourth generation (4G) cellular network has acted as a bridge between telecommunication technology and daily life applications. In this paper, we present an investigation into a telepresence wheelchair in outdoor environments employing cellular network infrastructure instead of using local wireless networks in indoor environments. Experiments were carried out to demonstrate remot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 7 publications
2
16
0
Order By: Relevance
“…The initial results of the first experiment (telepresence wheelchair based on WebRTC) show that the connection time of WebRTC is faster with less latency than the Skype platform. These results are entirely supported by previous studies [20,21,24] which demonstrated real-time telepresence. This result revealed that WebRTC processing is done at the user level, which reduces the delay in processing and connection time.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The initial results of the first experiment (telepresence wheelchair based on WebRTC) show that the connection time of WebRTC is faster with less latency than the Skype platform. These results are entirely supported by previous studies [20,21,24] which demonstrated real-time telepresence. This result revealed that WebRTC processing is done at the user level, which reduces the delay in processing and connection time.…”
Section: Discussionsupporting
confidence: 89%
“…This result revealed that WebRTC processing is done at the user level, which reduces the delay in processing and connection time. Moreover, the transmission rate of WebRTC is able to adapt to the available bandwidth of the network, whereas Skype platform adjusts the video resolution to adapt to the network condition [20,21,24]. Similar findings were observed by another study reported in [25], which indicated that the WebRTC-based video conference system could perform well on the network less than 1 Mbps of bandwidth capacity.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Researchers have recently developed various prototypes for telepresence systems. Typical examples of such works included [1][2][3] in which the authors developed telepresence robots based on existing video conferencing platforms using Voice over Internet Protocol (VoIP) and Skype platform [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…Our research group has recently demonstrated a telepresence wheelchair based on the Internet protocols and the Skype cross-platforms [3,7]. Our prior attempts have achieved some degrees of success in software and hardware development.…”
Section: Introductionmentioning
confidence: 99%